2009
DOI: 10.1002/mop.24235
|View full text |Cite
|
Sign up to set email alerts
|

A novel symmetrical monopole antenna for dual‐broadband operation

Abstract: The antenna gains are shown in Figure 10. The proposed antenna possessed a moderate gain, and a sharp decrease of the gain is presented at the band-notched frequencies. CONCLUSIONA band-notched printed monopole antenna is investigated in this article, which presents a band-notched performance in the WLAN band by cutting a slot on the patch. Details of the proposed UWB and band-notched design are discussed, results of impedance bandwidth and radiation characteristics are given, and the parameters which affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Via iterative trials, finally, the optimal geometrical values for the strips, the feedline, and the ground plane were all obtained and as those denoted in Figure 1. The overall size of the proposed antenna, including the ground plane, is only 20 × 30 mm 2 , which has a size reduction of about 31%, comparing to the reported antenna with the similar function [10].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Via iterative trials, finally, the optimal geometrical values for the strips, the feedline, and the ground plane were all obtained and as those denoted in Figure 1. The overall size of the proposed antenna, including the ground plane, is only 20 × 30 mm 2 , which has a size reduction of about 31%, comparing to the reported antenna with the similar function [10].…”
Section: Introductionmentioning
confidence: 83%
“…For this, one interesting candidate seems belong to the planar antenna, especially the printed prototypes. It has been reported that this kind of antenna can be designed as various types such as the inverted-F antennas [1,2], the coplanar waveguide (CPW)-fed antennas [3][4][5][6][7], and the microstripline-fed antennas [8][9][10][11][12][13][14] for broad-or multi-band operation, which is suitable for two multiband wireless communication systems such as 2.4/5.2/5.8 GHz (2.4-2.484/5.15-5.35/5.725-5.825 GHz) wireless local area network (WLAN) and the 2.5, 3.5/5.5 GHz (2.5-2.69, 3.4-3.69/5.25-5.85 GHz) worldwide interoperability for microwave access (WiMAX). However, most of these designs are either complex in antenna structure or large in antenna size for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the omni-directional radiation characteristics of monopole antenna make them very suitable for indoor applications. In published literature, many configurations of antennas with dual-band operating characteristics have been reported for WLAN applications [5][6][7][8][9][10], such as G-shaped monopole [5,6], double-T monopole [7], split-ring monopole [8], meander line monopole [9,10], and so on. However, among theses designs, most of them are either larger in size or complex in structure for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed antenna with microstrip-fed structure is compact, which has a total size of 18 mm × 28 mm × 1 mm. The dualband operation of the proposed antenna is achieved by the dual resonant structures [5][6][7]. By changing related parameters of the introduced structure, dual-band characteristics can been adjusted easily.…”
Section: Introductionmentioning
confidence: 99%
“…The wireless systems that are currently popular are the wireless local area network (WLAN), which operates in the 2.4/5.2/5.8 GHz frequency bands, and the Worldwide Interoperability for Microwave Access (WiMAX) system, which operates in the 2.5/3.5/5.5 GHz frequency bands. Currently, several dual-band and tri-band printed antennas have already been reported [1][2][3][4]. Unfortunately, most of these antennas can only satisfy either the WLAN standards in the 2.4/5.2/ 5.8 GHz bands (2.4-2.484/5.15-5.35/5.725-5.875 GHz) [1,2] or the WiMAX standards in the 2.5/3.5/5.5 GHz bands (2.4-2.6/ 3.3-3.8/5.25-5.85 GHz) [3,4].…”
Section: Introductionmentioning
confidence: 99%